Pro-oxidant activity of α-tocopherol during photooxidative degradation of polyolefins. ESRI and IR microspectroscopy studies. (April 2017) - Pilař, Jan; Šlouf, Miroslav; Michálková, Danuše; Šloufová, Ivana; Vacková, Taťana; Dybal, Jiří
Abstract: Photooxidation processes inside high-density polyethylene (HDPE) and cyclic olefin copolymer (COC) poly(ethylene- co -norbornene), both stabilized with biological antioxidant α-tocopherol (α-T-OH), has been investigated. Plaques made of the polymers stabilized with α-T-OH were subjected to long-term accelerated weathering in a Weather-Ometer (WOM). Concentration profiles of radicals generated in the plaques in dependence on WOM exposure time were determined by electron spin resonance imaging (ESRI). Concentration profiles of oxidation products and stabilizer, together with local crystallinity profiles inside the polymer plaques were determined by infrared (IR) microspectroscopy. The ESRI and IR profiles, supplemented by light microscopy (LM) and microindentation hardness measurements (MH), revealed the heterogeneity of the oxidation process and, surprisingly, the pro-oxidative activity of α-T-OH. Increasing concentration of products of polymer oxidation was found in the surface layers of the plaques stabilized with α-T-OH since the beginning of WOM treatment unlike the same control experiments with polymer plaques stabilized with HAS Tinuvin ® 770, where no oxidation products were observed after the same treatment before HAS depletion. We have confirmed that α-T-OH exhibits antioxidant activity during thermooxidation but it acts as a pro-oxidant agent during photooxidation. Graphical abstract: